ALUMINUM BOX BUNDLING PRESS - Iosif DUMITRESCU; Răzvan Bogdan ITU; Vilhelm Itu (Fiabilitate şi Durabilitate)
In municipal solid waste, aluminum is the main nonferrous metal, approximately 80- 85% of the total nonferrous metals. The income per ton gained from aluminum recuperation is 20 times higher than from glass, steel boxes or paper recuperation. The object of this paper is the design of a 300 kN press for aluminum box bundling.